Poor Workers in Rich Democracies: On the Nature of In-Work Poverty and Its Relationship to Labour Market Policies - Rod Hick; Ive Marx (Institute of Labor Economics (IZA), 2022)
The working poor were long thought of as people toiling away in lousy, under-protected and underpaid jobs in places like fast-food joints, supermarkets, hotels and bars. The perfidious consequence of that perception was that in-work poverty was seen as a non-issue in countries with extensive labour protections, especially in countries with minimum wages at significant levels. The idea that the working poor were only to be found in the so-called "liberal" economies lacking strongly organized labour and proper regulatory correction has turned out to be completely wrong. In-work poverty exists in all rich economies. But what, exactly, do we mean by in-work poverty? How is it related to labour market trends and also to policies? And how might governments look to successfully tackle the problem of working poverty? In this paper, a draft chapter forthcoming in Clegg, D. and Durazzi, N. (eds), Research Handbook of Labour Market Policy in Rich Democracies, with Edward Elgar we provide some answers to these important questions.
Keywords: J08; 330; low pay; poverty; labour market policies